Nkanelo wa nemesis eka tsalwa ra Ndlandlati ya Malenga hi A.D Mahatlani na Mibya ya Nyekanyeka hi B.K.M Mtombeni - Ngobeni, E. (University of Limpopo, 2013)
The main aim of this study is to analyse nemesis in Ndlandlati ya Malenga by A.D Mahatlani and Mibya ya Nyekanyeka by B.K.M Mtombeni. Chapter one outlines the background of the research. This chapter deals with the theme and the methodology of the reseach. This chapter outlines the different studies that were done on Xitsonga Literature at Honours, Masters and Doctoral levels. This chapter also shows the methodology, the scope and definitions of important terms that are used in this study. Chapter two defines characterization on its broadness, looking at Ndlandlati ya Malenga by A.D Mahatlani and Mibya ya Nyekanyeka by B.K.M Mtombeni. Chapter three outlines the biographies of the A.D Mahatlani, the author of Ndlandlati ya Malenga and B.K.M Mtombeni, the author of Mibya ya Nyekanyeka. This chapter also deals with the summary of the book called Ndlandlati ya Malenga and Mibya ya Nyekanyeka. ix Chapter four deals with the analysis of nemesis in Ndlandlati ya Malenga by A.D. Mahatlani and Mibya ya Nyekanyeka hi B.K.M. Mtombeni. This chapter depicts different characters who had problems or challenges in life and the result thereof by failing to accept the situation they found themselves in, by failing to resolve them. Chapter five presents a summary of findings and recommendations of the research
Thesis (M.A. (African languages)) --University of Limpopo, 2013
Keywords: Analysis of nemesis; Tsonga literature; African literature|xHistory and criticism